Anti-corrosion Behavior of Al2O3@SiO2 Composite Electrokinetic Nanoparticles on Reinforced Concrete - Pang, Fangjie; Zhao, Wenyan; Ding, Yuxing; Lu, Wenmin; Yan, Yiru; Jiang, Jinyang; Wang, Zengmei (Journal of advanced concrete technology, 2023)
Electromigration of electrokinetic nanoparticles in concrete structures is an effective approach to enhancing pore structure and retarding the transportation rate of chloride ions. However, there is limited research on the impact of stable positively charged electrokinetic nanoparticles on the corrosion behavior of reinforced concrete. In this paper, the structure of reinforced concrete was optimized by controllably Al2O3@SiO2 composite electrokinetic nanoparticles driven by a direct current electric field, and the influence of synthesis parameters, such as reaction time and temperature, on the modified silica sol was discussed. After 14 days of electromigration, spherical nanoparticles were found at depths of 5 to 10 mm inside the concrete. The porosity of the concrete reduced from 26.2% to 9.9%, with the most desirable pore size decreasing from 96.3 nm to 40.3 nm. After 9 months of dry and wet cycling, the electrokinetic nanoparticle-treated samples demonstrated a higher corrosion potential and a lower corrosion current density. Electromigration of electrokinetic nanoparticles slowed the transportation rate of chloride ions and significantly reduced their content in the concrete. Additionally, the Al2O3@SiO2 layer coating on the steel further enhanced its anti-corrosion ability, effectively inhibiting the corrosion of the reinforcement in concrete.